Effectiveness of digital learning on students’ higher order thinking skills - Mat, Hamidah; Mustakim, Siti Salina; Razali, Fazilah; Ghazali, Norliza; Minghat, Asnul Dahar (International Journal of Evaluation and Research in Education (IJERE), 2024)
In the realm of education, learning and instructional activities play a crucial role in cultivating lasting and meaningful comprehension among science students. This research aims to evaluate the effectiveness of the i-Genius module in enhancing students’ performance in science. The i-Genius module’s development adhered to the ADDIE model, and two specific research questions were formulated: i) is there a statistically significant difference in mean scores between the experimental and control groups? and ii) to what extent can i-Genius contribute to students’ conceptual evolution compared to traditional methods? To address these questions, a sequential mixed-method approach involving interviews, pre-tests, and post-tests was implemented in two distinct schools in the Seremban District. The experimental group comprised 35 participants, and the control group also included 35 students with similar characteristics. Student performance, assessed through pre-test and post-test mean scores, revealed that students exposed to i-Genius achieved significantly higher scores than those exposed to traditional methods in the post-test (t(68)=8.37, p<0.05). This study’s implications lie in its practical application within the school context, offering an alternative instructional tool for teaching science and presenting an instructional model to guide teachers in formulating strategies that encourage problem-posing within the science curriculum.